Effective mitigation of the thermal short and expansion mismatch effects of an integrated thermal protection system through topology optimization. (1st June 2017) - Yang, Qiang; Meng, Songhe; Xie, Weihua; Jin, Hua; Xu, Chenghai; Du, Shanyi
Abstract: This paper presented an innovative integrated Thermal Protection System (ITPS) with both thermal insulation and load bearing capabilities. Thermal short and thermal expansion mismatch effects are the key design challenges of an ITPS. The objective of this paper is to establish a topology optimization method against these two effects. The thermal-mechanical analysis model of an ITPS is presented first. Then, the limits of size optimization method in solving these two effects are studied through design of experiments. A topology optimization model of the web is established using loads and boundary conditions extracted from the global ITPS model. Optimizations were carried out under different load cases. Comparisons of structural responses, including thermal structural stress, were made between the original, optimized ITPS, and ITPSs with the same maximum back face temperature. The results showed that a reduction of 12.05% in maximum bottom temperature and a decrease of 11.2% in overall maximum structural stress had been achieved. The proposed method can effectively mitigate the thermal short and thermal expansion mismatch effects of the ITPS simultaneously. Highlights: The structure design challenges of the ITPS are studied in detail. A topology optimization method of the ITPS is established. The proposed topology optimization method can alleviate thermal short and expansion mismatch effect at the same time.